Day 2 Tue, November 01, 2022 2022
DOI: 10.2118/210972-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Ultra-Selective Solvent to Reduce the Cost to Capture CO2 from a H2S-Rich Natural Gas

Abstract: The contribution of CO2 present in natural gas to the total GHG emissions of the gas plant can be significant (up to 20% for Middle East Gas). When both H2S and CO2 are present, the CO2 capture cost is currently very high. The method developed to tackle this challenge is an innovative architecture of the acid gas treatment chain based on a new ultra-selective absorption process. The redesigned acid gas treatment architecture is detailed and compared with available technologies on the market. The technical cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…To simultaneously respect the asymmetrical H 2 S (<4 ppm) and CO 2 (<2.0–2.5 vol %) specification, a selective solvent can be used that preferentially absorbs H 2 S over CO 2. Techno-economic studies have shown that a further increase of the selectivity might lower the cost of CO 2 capture from natural gas containing H 2 S. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To simultaneously respect the asymmetrical H 2 S (<4 ppm) and CO 2 (<2.0–2.5 vol %) specification, a selective solvent can be used that preferentially absorbs H 2 S over CO 2. Techno-economic studies have shown that a further increase of the selectivity might lower the cost of CO 2 capture from natural gas containing H 2 S. , …”
Section: Introductionmentioning
confidence: 99%
“…Physical solvents can be used for bulk selective H 2 S removal. Many molecules can be used, ,, and common examples are the Rectisol, Purisol, and Selexol processes. The selectivity is thermodynamic …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation